Vitamin D intake, calcium intake and physical activity among children with wrist and ankle injuries and the association with fracture risk. Issue 2 (June 2019) - Alshamrani, Hassan A; Alloub, Hana; Burke, Derek; Offiah, Amaka C
Background: Several studies have revealed a substantial increase in the incidence of fractures in children in the past few decades. Aim: To assess the strength of the association between suggested risk factors and fracture prevalence in children. Method: A cross sectional observational study. Children aged 6–15 years and their guardians presenting to the Emergency Department of a single tertiary paediatric hospital were recruited. Self-reported data on vitamin D intake, calcium intake and physical activity were collected. All participants had a radiograph of their injured limb reported by a consultant radiologist, on the basis of which they were classified into fracture or no fracture groups. Statistical analysis included descriptive statistics and binary logistic regression. Results: Of the 130 patients recruited, 53 (41%) had sustained a fracture. The overwhelming majority of children (98%) did not consume the recommended daily dietary amount of vitamin D (400 IU/day). Low calcium intake and low levels of physical activity were also ascertained. However, there were no significant differences between fracture and no fracture groups for vitamin D intake, calcium intake or physical activity. Both site of injury (wrist) and sex (male) were associated with increased fracture risk ( p = 0.001 and p = 0.05, respectively). Logistic regression showed a statistically significant relationship between calcium intake and fracture risk (every additional unit of calcium consumption (mg/day) decreased the likelihood of fracture by 0.002, 95% confidence interval, 0.001–0.003). Conclusions: Low dietary intake of calcium and vitamin D and low levels of physical activity were evident. Fracture risk was significantly associated with reduced calcium intake but showed no association with vitamin D intake or physical activity.